Coexistence of Familial Mediterranean Fever and Rheumatoid Arthritis in A Case - Yasemin Turan; Ömer Faruk Şendur; Işıl Karataş Berkit (Archives of Rheumatology, 2010)
Familial Mediterranean Fever (FMF) is an autosomal recessive polysystemic disease characterized by attacks of relapsing and self-limiting fever, peritonitis, pleuritis and arthritis. Rheumatoid Arthritis (RA) is an erosive, chronic, inflammatory disease that affects hand and ankle joints in polyarticular type and causes deformities. To our knowledge, development of RA in a patient with FMF has not been reported before. Therefore, we present a 48 years old case who developed RA during the course of FMF. (Turk J Rheumatol 2010; 25: 44-6)